Effect of Lubrication on the Changes in Tensile Properties of Cotton Sewing Thread at Different Stages of Sewing (Journal of Fiber Bioengineering and Informatics, 2019)
Friction forces play a very important role in performance of sewing thread during the sewing process. Various finishes are applied over sewing threads to reduce the friction forces, which help in masking the basic properties of sewing thread and reduce the yarn to metal friction and yarn to yarn friction. In this paper, the effect of lubrication (%) on tensile properties of sewing thread is measured at four sewing stages: before sewing, after dynamic loading at the tension regulator, after passage through the needle and fabric assembly, and after bobbin thread  interaction. It is found that as the lubrication per cent increases friction coefficient decreases, in general. Due to this, the loss in tensile properties of the sewing threads during sewing decrease. Tenacity loss decreases during all sewing  stages, as the lubrication percentage increases.
Keywords: Lubrication; Sewing Stages; Tenacity